Assistance To Improve Social Welfare Through Religious Awareness And Psychological Well-Being Based On Family Development Sessions For Muslim Communities Receiving Social Welfare In Sawoo District, Ponorogo Regency - Fatkhur Rohman Albanjari; Yusuf Hamdani Abdi; Nugraheni Fitroh R.Syakarna; Mazuri Binti Abd Ghani (International Journal Of Community Service, 2024)
This research aims to improve the social welfare of Muslim community recipients of social assistance in Sawoo District, Ponorogo, through increasing religious awareness and psychological well-being based on Family Development Session (FDS). The hypothesis proposed is that increasing religious awareness through FDS can improve social welfare. The research methods include needs identification, implementation of FDS sessions, and evaluation of program impacts through social welfare measurement before and after the intervention. The training uses a psychological capital approach (HERO: hope, self-efficacy, resilience, optimism) with an experiential learning method. The study participants were 60 people from various age groups. Religious orientation was measured using the Religious Orientation Scale (ROS) and psychological well-being was measured using the Ryff Scale of Psychological Well-being. The results of the data analysis showed a significant improvement in religious awareness and psychological well-being of participants after training, supporting the hypothesis that increased religious awareness through FDS contributes to social well-being.